Entre as fronteiras da regulação managerial da ideia de qualidade e o discurso da praxis dos técnicos de radiologia nos hospitais públicos da Região Algarve - Abrantes, António (2013)
We present in this paper the main results of a research about organizational factors of health technology quality in radiology departments of public hospitals from Algarve Region. Qualitative analysis of the diagnosis allowed us to generate four clusters of verbalizations. The most representative cluster is the clusters 2 (36.26%) "autonomous regulation of work context improvement". The following is cluster 4 (27.47%) "Perspectives of managerial regulation control of quality improvement." Cluster 3 (20.88%) gives us a set of verbalizations about "professional autonomy" boundaries and the logics of "organizational control". Cluster 4 (15.38%), interpreted as "being responsible", brings the field of possibilities of a idea of radiographers as a producer and protagonist of rules in these organizations.